2008
DOI: 10.7326/0003-4819-148-2-200801150-00010
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for Improving Palliative Care at the End of Life: A Systematic Review

Abstract: Strong to moderate evidence supports interventions to improve important aspects of end-of-life care. Future research should quantify these effects and address the generalizability of insights across the conditions and settings of the last part of life. Many critical issues lack high-quality evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
322
1
24

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(355 citation statements)
references
References 139 publications
4
322
1
24
Order By: Relevance
“…The absence of a shared understanding of how end of life is recognised, or at what point end of life is defined for people with dementia, means that research that focused on improving symptom assessment for people with advanced dementia, on needs assessment in care homes, and on communication and the involvement of people with dementia in decision making were not included in the review (Fossey et al, 2006;Hancock et al, 2006;Zwakhalen et al, 2006). Data extraction ceased in 2006, however a rapid review of research and reviews published up till 2008 (Birch and Draper, 2008;Di Giulio et al, 2008;Lorenz and Lynn, 2008) indicate that the research focus and methods and findings discussed in this paper have not dramatically changed, and that there are still very few intervention studies that include people with dementia who are living at home or in a care home.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a shared understanding of how end of life is recognised, or at what point end of life is defined for people with dementia, means that research that focused on improving symptom assessment for people with advanced dementia, on needs assessment in care homes, and on communication and the involvement of people with dementia in decision making were not included in the review (Fossey et al, 2006;Hancock et al, 2006;Zwakhalen et al, 2006). Data extraction ceased in 2006, however a rapid review of research and reviews published up till 2008 (Birch and Draper, 2008;Di Giulio et al, 2008;Lorenz and Lynn, 2008) indicate that the research focus and methods and findings discussed in this paper have not dramatically changed, and that there are still very few intervention studies that include people with dementia who are living at home or in a care home.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are effective for the management of dyspnea, but are underused by physicians because of concerns about respiratory depression [62]. The American College of Physicians (ACP) recommends treatment with short-acting opioids, because several randomized controlled trials have shown the beneficial effects of systemic opioids in the control of dyspnea [63,64]. Although small series describe relief of dyspnea with the administration of nebulized opioids [65], randomized controlled trials and a Cochrane review did not show that nebulized opioids are effective for dyspnea [66].…”
Section: Dyspneamentioning
confidence: 99%
“…[15][16][17][18] During this time, palliative care treatment plans can be implemented, in place of or in addition to existing care plans, to reduce suffering and improve end-of-life care. 12,19,20 Despite the benefits of palliative care [18][19][20][21][22][23][24][25] and its growth in recent years, 20,25,27 it is not always available for inpatients, partly because the subspecialty palliative care workforce is not currently sufficient to reach all patients dying in hospital settings and partly because practitioners do not recognize shifts in patient trajectory indicating the need for palliative care consultation. [26][27][28][29][30][31][32] In an environment focusing on "cure," transition away from disease-modifying treatments to symptom control can seem counterintuitive.…”
Section: Introductionmentioning
confidence: 99%